2023
DOI: 10.1002/cta.3542
|View full text |Cite
|
Sign up to set email alerts
|

An improved robust coupled sliding mode control strategy for solar photovoltaic‐based single‐phase inverters

Abstract: Solar photovoltaic (SPV)-based single-phase inverters are universally accepted and commercially utilized renewable power converter system. Generally, the magnitude of the inverter output is perturbed on load variations, and the intermediate DC-DC boost converter output is perturbed because of the solar availability. The main intermediary component is the DC-Link capacitor. The regulation of DC-Link voltage is the key factor in maintaining the stability of the system with bilateral power converters. In the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Therefore, a coupled SMC can address the DC links voltage regulation. The simulation results showed that this scheme can achieve the stability of DC link voltage regulation in the power system [ 9 ]. T Chen et al proposed an observer-based adaptive neural network backstepping sliding mode controller to address stability issues in power systems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a coupled SMC can address the DC links voltage regulation. The simulation results showed that this scheme can achieve the stability of DC link voltage regulation in the power system [ 9 ]. T Chen et al proposed an observer-based adaptive neural network backstepping sliding mode controller to address stability issues in power systems.…”
Section: Related Workmentioning
confidence: 99%
“…In the above equation, 0 � η(t) � h + η M , η M represents the maximum allowable delay upper bound. Substituting Eq (8) into Eq (2), the time-delay model of interconnected power system LFC dependent on ACE can be obtained as shown in Eq (9).…”
Section: Plos Onementioning
confidence: 99%